Islāmic guidelines for women to work and hold public office positions - Abdul Karim, Asar; Ghalia, Bouhedda (International Journal of Science and Research (IJSR), 2016)
The issue of women working outside home and holding public office positions is a never ending issue in Muslim world. Researchers have concluded in their research that a woman is permissible to work outside home as well as to hold any public office positions as long she follows Islāmic guidelines. In fact, a truly Islāmic society actually must comprise of women who join the working forces. A part of discussing the main flaws of the scholars’ arguments; this paper also discusses the Islāmic guidelines for women to work outside home and to hold public office positions. By the detailed discussion about the Islāmic guidelines, it is hoped that the disagreement opinions about the issue could be eliminated, or at least it can be reduced to a minimum level.